Nitrites in Meat Products in Serbia: Harmful or Safe? - Jasna Kureljušić; Jelena Maletić; Slavoljub Stanojević; Branislav Kureljušić; Jelena Petković; Ana Vasić; Tanja Bijelić (Foods, 2025)
Nitrate and nitrite, commonly added to meat products as sodium or potassium salts, serve multiple functions such as developing characteristic flavor, inhibiting microbial growth, and controlling rancidity by preventing lipid oxidation. Nitrites are recognized for their potential health risks to humans. The present research aimed to determine the amount of nitrite in four meat product categories in Serbia over a period from 2015 to 2021. A total of 923 samples were analyzed, including 293 finely chopped sausages, 203 coarsely chopped sausages, 160 canned meats, and 267 smoked meats. The smoked meat category consisted of eight distinct products, such as smoked pork ribs, sirloin, and chicken drumsticks. An ISO 2918 method was used to measure the nitrite content. The average nitrite content, expressed as sodium nitrite (NaNO2), was found to be 61.5 mg/kg in finely chopped sausages, 57.6 mg/kg in coarsely chopped sausages, 48.4 mg/kg in canned meat, and 41.8 mg/kg in smoked meat. The results collectively demonstrate nitrite concentrations within regulatory limits. In conclusion, the nitrite concentrations in all tested products were below the maximum allowable limits as per national and European regulations, ensuring compliance with safety standards while highlighting the importance of continuous monitoring to mitigate public health risks.